KEADILAN GENDER DALAM ISLAM (Telaah Atas Diskursus Hak Rujuk Perempuan dalam Hukum Keluarga Islam) - Muhammad Aziz; Ahmad Hanif Fahruddin (Akademika, 2021)
Religius teachings that are considered to have long oppressed womenthe teachings that have been domination by men have been used as a justification for community perception that are very detrimental to women.however,this criticism of gender inequality in discusseions with human rights does not only return to the misperception of the people.feminists also maintain a great deal about the concept of humen rights it self.fundamental criticism by questioning the return of international law to its maker. The qur’an has the principle that men and women are the same as servants, because men and women are created from the same subtance (kholifatullah fiilardh),and the same obligations ( liya’budun) however,in the matter of reconciliation,the ulama’ agree that reconciliation is an absolute right of the husband. In the gender perspective if you see some possible understanding that women can submit referals as their right to their husband by conducting a new analysis of  the issue of referral rights’ which so far has been suggested to be dominated by men ( husband) by redeeming the rights of husband who was given to him. And with the khulu’ also the wife also has the right to the right of reconciliation to the husband who has dropped divorce on him.